Major fishery events in Kerguelen Islands: Notothenia rossii, Champsocephalus gunnari, Dissostichus eleginoides – Current distribution and status of stocks ... - Duhamel, Guy; Pruvost, Patrice; Bertignac, Michel; Gasco, Nicolas; Hautecoeur, Mélyne (Cybium, 2011)
The large-scale trawl exploitation targeting virgin stocks of marbled notothenia (Notothenia rossii) off the Kerguelen Islands occurred after the discovery by the Soviet Union scouting fishing fleet of the fishing grounds in the early 1970’s. The fishery shifted to icefish (Champsocephalus gunnari) and grey notothen (Lepidonotothen squamifrons) when overexploitation on the shelf and surrounding banks resulted in the sharp decline in the catches of marbled notothenia. The creation of the French EEZ in 1978 closed the free fishery but did not stop the reduction of the biomass of exploited stocks. The SKALP first surveys (1987 and 1988), despite bias in the protocols, revealed the poor state of biomass in these shelf stocks. Only the icefish fishery maintained a series of strong cohorts with harvestable biomass, which eventually declined and lead to its closure in the 1990’s. However, the more recent biomass survey (POKER, 2006) showed no recovery in these stocks. Possible changes between species ...